IMPLEMENTASI METODE TAHDIDUL AYAT DALAM MENINGKATKAN KEMAMPUAN MENGAJI MAHASISWA JURUSAN SISTEM INFORMASI FAKULTAS SAINS DAN TEKNOLOGI UIN ALAUDDIN MAKASSAR - Hastuti; Besse Ruhaya (al-Afkar, Journal For Islamic Studies, 2021)
The qur 'an is a living guide for muslims and reading it is worth worship. The qur 'an is so noble that it must read it well and properly in order to obtain worship and glory. To read the qur 'an well, it has a code or rule which is with a tajwid. Therefore, the tahdidul ayat method is one of tahsin's methods for improving the ability to read the qur 'an. Thus, the study aims to introduce the qur 'an method by examining the ability to read the qur 'an in science students and technology department information system of uin alauddin makassar and then analyzing the implementation of the method to enhance student teaching. To examine both items, the study uses descriptive qualitative methods to collect data through literature, observation, and documentation. So that the results obtained that the ability of students to recite the Information System of qur'an in Faculty of Science and Technology of UIN Alauddin Makassar is very low so that it requires guidance for tahsin with a special method, namely Tahdidul Ayat. The Tahdidul Ayat method is a tahsin method with verse classification. The method is very appropriate to be used for various groups, especially for students because the material is simple and practical so that it is easy to understand. The implementation of this method goes through three stages : 1) initial activities including muqaddimah/opening, apperception, and repetition of material. 2) guidance includes providing material, Qur'an exercises, and classification of verses. 3) reading / memorizing.